2000
DOI: 10.1149/1.1394103
|View full text |Cite
|
Sign up to set email alerts
|

Electroreduction of Nitrate and Nitrite Ion on a Platinum-Group-Metal Catalyst-Modified Carbon Fiber Electrode Chronoamperometry and Mechanism Studies

Abstract: The mechanisms of nitrate and nitrite ion electroreduction on a carbon fiber electrode modified with platinum group metal catalyst are studied. Chronoamperometry studies reveal that two different mechanisms exist in two cathodic regions. A plot of log i vs. E reveals the presence of adsorption pseudocapacitance and is supported by impedance measurement at the electrode/solution interface. In the Ϫ600 to Ϫ800 mV (Ag/AgCl) potential region, the Tafel slope for nitrate ion reduction varies between ca. 221 and 236… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 18 publications
4
32
0
Order By: Relevance
“…Even though at high cathodic potentials, where the rate of hydrogen evolution is high, ammonia is the predominant product [4,27,29,32] the present work shows that at high cathodic potentials, unexpectedly, the main product on tin is nitrogen gas having both a high %S (92%) and a high rate of formation.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Even though at high cathodic potentials, where the rate of hydrogen evolution is high, ammonia is the predominant product [4,27,29,32] the present work shows that at high cathodic potentials, unexpectedly, the main product on tin is nitrogen gas having both a high %S (92%) and a high rate of formation.…”
Section: Introductionmentioning
confidence: 52%
“…It was proved that the conversion of nitrate to the nontoxic nitrogen gas is difficult since it is one of the eight possible products, NO 2 , NO 2 − , NO, N 2 O, N 2 , NH 2 OH, NH 3 and NH 2 NH 2 . When the supporting electrolyte is basic or neutral, the main by-products are nitrite and ammonia; furthermore, in acid electrolyte hydroxylamine and hydrazine have been also detected [27]. Nitrogen gas was detected on various metals and alloys, such as Cd (70-75%) [28], Pd-Cu (50%) [7], Pb (22%) [4], Sn85-Cu15 (34%) [29], Pd-Sn-Au (34%) [30], Sn-Pt (37%) [31] and Pd-Rh (94%) [32].…”
Section: Introductionmentioning
confidence: 99%
“…On iridium-modified carbon fiber electrode, NO 2 adsorption is the rate-determining step [9]. The experimental results indicate that: ± immediately after the desorption of hydrogen, a cathodic reduction peak results on a positive scan, ± current density increases nonlinearly with increasing nitrate concentration, ± the amount of reduced nitrate and evolved hydrogen was greater at ±950 mV relative to the results obtained at a potential of ±850 mV.…”
Section: Inhibition Kinetics For Nitrate Ion Electroreductionmentioning
confidence: 79%
“…The reduction mechanism for nitrate is very complex and involves more than one pathway [9]. In [10], Dibyendu showed that the first two steps of nitrate reduction on iridiummodified fiber electrode can be represented as:…”
Section: Inhibition Kinetics For Nitrate Ion Electroreductionmentioning
confidence: 99%
See 1 more Smart Citation